Apparatus at U.S. Department of Agriculture facility (1950)
General view of an unidentified apparatus at an unidentified U.S. Department of Agriculture facility.
Keywords: Nitrogen fertilizer industry; Scientific apparatus and instruments; United States. Department of Agriculture; United States. Bureau of Chemistry and Soils